Closed-Loop Transcutaneous Auricular Vagal Nerve Stimulation: Current Situation and Future Possibilities - Yu, Yutian; Ling, Jing; Yu, Lingling; Liu, Pengfei; Jiang, Min (Frontiers in Human Neuroscience, 2022)
Closed-loop (CL) transcutaneous auricular vagal nerve stimulation (taVNS) was officially proposed in 2020. This work firstly reviewed two existing CL-taVNS forms: motor-activated auricular vagus nerve stimulation (MAAVNS) and respiratory-gated auricular vagal afferent nerve stimulation (RAVANS), and then proposed three future CL-taVNS systems: electroencephalography (EEG)-gated CL-taVNS, electrocardiography (ECG)-gated CL-taVNS, and subcutaneous humoral signals (SHS)-gated CL-taVNS. We also highlighted the mechanisms, targets, technical issues, and patterns of CL-taVNS. By reviewing, proposing, and highlighting, this work might draw a preliminary blueprint for the development of CL-taVNS.